Biótipos de novilhos superjovens Aberdeen Angus abatidos com mesmo grau de acabamento na carcaça - Arboitte, Miguelangelo Ziegler (2010)
The objective of this study was to evaluate the performance and carcass characteristics of cattle breed Aberdeen Angus steers of small and medium frame score slaughtered the same degree of completion of housing (average 6.39 mm). To 18 steers were used with age and weight of 298 days and 202.17 kg at entry into the confinement. The animals were confined for 158 days and slaughtered at average live weight of 430 days and 428.94 kg. The feed was composed of sorghum silage and concentrate in the ratio of 60:40 in the dry matter in the first 63 days and after 50:50 until slaughter. The frame was calculated using the formula F=-11, 548+0,4878*h*0,0289*ID+0,0000146*ID²+0,0000759*h*ID. Steers with medium frame score showed superiority in important aspects of marketing, as the initial weight (y=107.87+250.04B; P=.0002), final (y=308.14+32.07B; P=.0001), the empty body (y=255.07+30.74B; P<.0001) and hot carcass (y=153.91+21.09B; P<.0001) and cold (y=150.29+20.78B; P<.0001). Measures of muscle content as the Longissimus dorsi area in relation to cold carcass weight (ȳ=32.64-1.53; P=.0477) and empty body (ȳ=16.3-0.55B; P=.0419) were lower in of the carcass. Carcass conformation (P=.4660) Longissimus dorsi area in cm² (P=.6999),cushion thickness (P=.3578) were similar between the small and medium frame score. The commercial cuts, forequarter (ȳ=54.93+7.84B; P<.001), rib (ȳ=21.33+3.31B; P=.009) and back (ȳ=74.02+9.64B; P=.0003) in kg was higher in medium frame score. As a percentage cut back fell .18% with the incrase in frame score (ȳ=49-.18B P.0404). Weight tissue constituents of the carcass increased with the frame score of the steers, as on the percentage muscle tissue decreased by .57% (ȳ=61.63-.57B; P=.0410). The meat of Longissimus dorsi muscle of steers Aberdeen Angus of small and medium frame score showed intramuscular fat with a mean average of 10.11 points (P=.7034), red color with an average of 4.33 points (P=.3724), fine texture with a tendency to thin with an average 4.61 points (P=.3075) and the shear force with an average of 2.72 kg/cm² (P=.4004). Composition chemical of beef Longissimus dorsi muscle frame score steers Aberdeen Angus presented moisture with 72.27% (P=4355), crude protein of 19.34% (P=4150), lipid with 3.96% (P=9071), minerals with 4.43% (P=9842) and cholesterol to 50.25 mg/100g of meat (P=.2375). The small and medium frame score did not influence trhe fatty acids palmitic (P=.0790), stearic (P=.2455), oleic (P=.3046), linoleic (P=.9456), occurring change in the composition fatty acids myristic (y=1,85+0,12F; P=.043). The introduction of the frame score in studies of meat composition may be important in determining the frame score of steers with the nutritional features of the best meat. The medium frame score of Aberdeen Angus steers had higher head weight (y=9.35+.49B; P=.0212), feet (=5.38+.57B; P=.0059), tongue (y=.93+.05B; P=.0154), heart (y=1.45+.07B; P=.0183), inguinal adipose tissue (y=1.79+.21B; P=.0336) and adipose tissue is not part of the carcass plus to this in the meat (y=88.5+3.70B; P=.0086). Steers with small frame score were more (y=1.46-.08B; P=.0407) in the participation of the lungs in relation to empty body weight Aberdeeen Angus Steers. The small and medium frame score did not affect the participation of the rumen-reticulum, abomasums, omasum, intestines and contents of the gastrointestinal tract weight in relation to body weight an empty body weight.